The atlas of Hillforts of Britain and Ireland online - Pouncett, J (Archaeopress, 2019)
The Atlas of Hillforts of Britain and Ireland was a collaborative research project funded by the Arts and Humanities Research Council and carried out by the Universities of Oxford and Edinburgh, together with colleagues from University College Cork, Ireland. Building on a strong tradition of mapping dating back to the nineteenth century, the Atlas of Hillforts for the first time draws together evidence relating to all known hillforts – an iconic class of monument which forms the dominant component of settlement record in the first millennia BC and AD - on both sides of the Irish Sea. The digital version of the Atlas of Hillforts of Britain and Ireland was created using the ArcGIS platform, with the underlying data hosted on an ArcGIS Enterprise server and an accessible user interface created using Web AppBuilder for ArcGIS. It was launched at the end-of-project conference in June 2017 and has attracted over 275,000 visitors from 198 countries since then, with an average visit of over 6 minutes and more than 45 page views per visitor. The digital atlas has been used to promote National Parks, museums and public archives and has been highlighted as an invaluable research tool and educational resource for schools and universities.